Applying the Advocacy Coalition Framework to Understand the Process of Local Legislation in Indonesia - Alamsyah Alamsyah; Sri Suwitri; Kismartini Kismartini; Yuwanto Yuwanto (Faculty of Law, Sriwijaya University, Indonesia, 2019)
Making regulation is the primary function of the modern state. Current praxis shows how there is positive and negative cooperation among policy participant in the process of local legislation. Many Indonesian scholars give attention to the politics of law and citizens participation in understanding this process. However, they do not give detail analysis on cooperation among policy participant during the legislation process. Drawing on qualitative methods, this article applies the Advocacy Coalition Framework (ACF) to understand the process of local legislation in South Sumatra Province. This article selects The Provincial Regulation of South Sumatera No. 8 of 2016 on the Forest Fires Mitigation as a case study due to the nature of forest fires as the public problem that obtains attention from various actors. Several key informants representing the executive and the legislative at the local level is selected using the purposive technique as a source of primary data. The secondary data is collected from the official publication of the policy participant, newspaper, and social media. Using interactive models and NVIVO software to code and analyse research data, this article finds that the secondary policy belief (SPB) among policy participant could be similar partially or wholly. This similarity is the foundation of policy participant to make an advocacy coalition. This article identifies two advocacy coalition in legislation process of The Provincial Regulation of South Sumatera No. 8 of 2016 on the Forest Fires Mitigation: ‘the local wisdom’ coalition vs. ‘the no burning policy' coalition. This article discusses the findings and propose a new agenda for further research on local legislation process